ACID-BASE BALANCE - Évora, Paulo Roberto Barbosa; Garcia, Luis Vicente (Medicina (Ribeirao Preto), 2008)
A profound knowledge about variations in the acid-base balance is of utmost importance for both the correct diagnosis and the treatment of possible abnormalities. Here, the causes and consequences, as well as potential treatments of both respiratory and metabolic alkalosis and acidosis are discussed.